2017
DOI: 10.1038/nature24637
|View full text |Cite|
|
Sign up to set email alerts
|

NFS1 undergoes positive selection in lung tumours and protects cells from ferroptosis

Abstract: Environmental nutrient levels impact cancer cell metabolism, resulting in context-dependent gene essentiality1,2. Here, using loss-of-function screening based on RNA interference, we show that environmental oxygen levels are a major driver of differential essentiality between in vitro model systems and in vivo tumours. Above the 3–8% oxygen concentration typical of most tissues, we find that cancer cells depend on high levels of the iron–sulfur cluster biosynthetic enzyme NFS1. Mammary or subcutaneous tumours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
453
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 585 publications
(465 citation statements)
references
References 34 publications
12
453
0
Order By: Relevance
“…For example, mitochondrial Fe-S cluster biosynthesis is a process that is highly conserved in eukaryotic organisms from yeast to man (Lill and Muhlenhoff, 2006). In cancer cells, it has been reported that this biosynthetic pathway is essential for proliferation in the OXPHOS state (Arroyo et al, 2016) and for primary lung or metastatic tumors growing in high oxygen levels (Alvarez et al, 2017). This could be largely due to the numerous mitochondrial proteins that depend on Fe-S clusters for their functionality including complex I-III proteins, ACO1 and others making it a key upstream regulator of mitochondrial function (Cameron et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mitochondrial Fe-S cluster biosynthesis is a process that is highly conserved in eukaryotic organisms from yeast to man (Lill and Muhlenhoff, 2006). In cancer cells, it has been reported that this biosynthetic pathway is essential for proliferation in the OXPHOS state (Arroyo et al, 2016) and for primary lung or metastatic tumors growing in high oxygen levels (Alvarez et al, 2017). This could be largely due to the numerous mitochondrial proteins that depend on Fe-S clusters for their functionality including complex I-III proteins, ACO1 and others making it a key upstream regulator of mitochondrial function (Cameron et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, lipid peroxidation and ferroptotic cell death induced by perturbation of glutathione metabolism or GPX4 activity are fully suppressed by iron chelators like deferoxamine (DFO) and ciclopirox (CPX) . Disruption of the iron‐sulfur cluster biogenesis pathway enzyme cysteine desulfurase NFS1 sensitizes to ferroptosis in cultured cancer cells and in xenograft tumor models, most likely, by increasing the pool of free iron within the cell . Normally, iron is imported into the cell via the transferrin/transferrin receptor system and liberated from transferrin within lysosomes.…”
Section: The Role Of Iron In Lipid Peroxidation and Ferroptosismentioning
confidence: 99%
“…is suppressed by N-ethylmaleimide-sensitive fusion protein 1, an iron-sulfur cluster biosynthetic enzyme, thereby resisting against high oxygen tension and inducing lung tumor growth(Alvarez et al, 2017). Ferrostatin-1, as another ferroptosis inhibitor, remarkably impedes ART-induced ROS production and ferroptosis-dependent cell death in ovarian cancer(Basuli et al, 2017;Greenshields, Shepherd, & Hoskin, 2017).…”
mentioning
confidence: 99%